PrCuCoP / NF high-efficiency electro-catalysis composite material, preparation method and application

By co-doping Pr and Cu elements on CoP/NF substrates, the problem of high overpotentiality of electrohydrogen evolution catalysts at high current density is solved, and lower overpotentiality and higher overpotentiality are achieved The catalytic performance is suitable for industrial electrolysis hydrogen production technology.

CN119287413APending Publication Date: 2025-01-10XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411207206.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing electrohydrogen evolution catalysts have high overpotential under high current density, which limits the industrial application of electrolytic hydrogen production technology.

Method used

Using PrCuCoP/NF high-efficiency electrocatalytic composite material, by co-doping Pr and Cu elements on the CoP/NF substrate, an electrodeposition reaction is used to form a catalyst with high active sites, thereby improving catalytic performance.

Benefits of technology

The overpotential under acidic and alkaline conditions is significantly reduced, the reactivity and stability of the catalyst is enhanced, and excellent catalytic performance is maintained especially at high current density, and has high electrochemically active area and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287413A_ABST
    Figure CN119287413A_ABST
Patent Text Reader

Abstract

The invention provides a PrCuCoP / NF high-efficiency electro-catalysis composite material, a preparation method and an application. The high-efficiency electro-catalysis composite material is prepared by co-doping a monomer CoP / NF with a Pr element in PrCl3. 6H2O and a Cu element in Cu (NO3) 3. 3H2O. The Pr element on the surface of the high-efficiency electro-catalysis composite material exists in the form of Pr2O3, the Cu element exists in the form of CuO or CuO2, and generation of oxides provides more active sites for the hydrogen evolution reaction process under high current density. According to the high-efficiency electro-catalysis composite material disclosed by the invention, the application conditions of hydrogen evolution reaction are obviously broadened, and meanwhile, better overpotential can be achieved under acidic and alkaline conditions. Eta10 is 94 mV under the acidic condition, and Eta10 is 68 mV under the alkaline condition. Particularly, the high-efficiency composite material PrCuCoP / NF can keep better reaction activity under high current density (700mA cm <-2 >).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen evolution by electrolysis of water, relates to electrocatalytic materials, and specifically relates to a PrCuCoP / NF high-efficiency electrocatalytic composite material, a preparation method and an application thereof. Background Art

[0002] The production of hydrogen by electrolysis of water can effectively avoid the high pollution and high energy consumption problems of industrial hydrogen production. Therefore, finding efficient and widely applicable electrocatalysts is the key to driving the industrialization of water electrolysis hydrogen production technology. At present, the material for commercial hydrogen evolution is mainly the precious metal Pt. Although Pt has excellent hydrogen evolution performance, it is expensive and costly, which is not conducive to the large-scale industrial production of hydrogen evolution technology. Electrocatalytic hydrogen evolution technology is in line with the new energy policy advocated by the country and has the advantages of being effective and green. Transition metal-based composite electrocatalysts have been widely used in areas such as alleviating energy scarcity due to their low price and wide sources.

[0003] Electrocatalytic hydrogen evolution technology uses catalysts to achieve efficient utilization and conversion of electrical energy. Its electrocatalytic mechanism is as follows: the catalyst has a large number of catalytic active sites. The first step is that the proton on the active site captures an electron to form an adsorbed hydrogen atom (H ads ), a process called Volmer reaction. The second step is carried out in two ways: one is to react with H on the catalyst surface ads When the coverage rate is low, H ads tends to combine with protons and electrons to generate H2 molecules (Heyrovsky reaction); the second way is to ads When the coverage is high, two adjacent H ads The atoms combine to form H2 (Tafel reaction). H2 molecules are formed via the Volmer-Heyrovsky or Volmer-Tafel pathways.

[0004] Therefore, it is of great significance to increase the active sites of the catalyst and the exposure of the active sites as much as possible to improve the catalytic performance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a PrCuCoP / NF high-efficiency electrocatalytic composite material and its application to solve the technical problem that the overpotential of the electrohydrogen evolution catalyst in the prior art at high current density needs to be further reduced.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] A PrCuCoP / NF high-efficiency electrocatalytic composite material comprises a monomer CoP / NF substrate, wherein the monomer CoP / NF substrate is co-doped with a Pr element and a Cu element.

[0008] The molar ratio between the Pr element in the raw material of the Pr element and the Cu element in the raw material of the Cu element is (1 to 4):(1 to 4).

[0009] The present invention also has the following technical features:

[0010] Preferably, the Pr element exists in the form of Pr2O3; and the Cu element exists in the form of CuO and / or CuO2.

[0011] Preferably, the raw material of the Pr element is PrCl3·6H2O; the raw material of the Cu element is Cu(NO3)3·3H2O.

[0012] Preferably, the molar ratio between the Pr element in the raw material of the Pr element and the Cu element in the raw material of the Cu element is 1:(1-4) or (1-4):1.

[0013] Preferably, the Pr element and the Cu element are co-doped on the monomer CoP / NF substrate in the form of an electrodeposition reaction.

[0014] More preferably, the process of the electrodeposition reaction is: placed in a standard three-electrode system, the current density of the electrodeposition reaction is 0.25 mA, and the time of the electrodeposition reaction is 300 s.

[0015] The present invention also protects a method for preparing the PrCuCoP / NF high-efficiency electrocatalytic composite material as claimed in claim 1, the method comprising the following steps:

[0016] Step 1: Mix Co(NO3)3·6H2O, CH4N2O and NH4F, and add the mixture into water containing nickel foam to obtain a mixed solution.

[0017] Step 2: Add NaH2PO2 to the mixed solution in step 1 for phosphating to obtain a monomer CoP / NF substrate.

[0018] Step 3: dissolve the raw materials of the Pr element and the Cu element in water, and stir to form an electrolyte.

[0019] Step 4: Under stirring conditions, place the monomer CoP / NF substrate obtained in step 2 into the electrolyte obtained in step 3, and perform an electrodeposition reaction at room temperature.

[0020] Step 5: After the reaction in step 4 is completed, the mixture is repeatedly rinsed with water and vacuum dried to obtain a PrCuCoP / NF high-efficiency electrocatalytic composite material.

[0021] Preferably, in step 1, the specification of the NF is 2×4 cm 2 .

[0022] Preferably, in step 2, the phosphating time is 2 hours, the phosphating temperature is 300° C., and the phosphating heating rate is 2° C. / min.

[0023] Preferably, in step five, the vacuum drying temperature is 60° C. and the vacuum drying time is 6 hours.

[0024] The present invention also protects the use of the PrCuCoP / NF high-efficiency electrocatalytic composite material as a catalyst for electrocatalytic hydrogen evolution at high current density.

[0025] Preferably, the conditions for electrocatalytic hydrogen evolution are: the reaction area of ​​the PrCuCoP / NF high-efficiency electrocatalytic composite material is 0.5×1 cm 2 , current density is 700mAcm -2 The solution for the hydrogen evolution reaction is an acidic solution or an alkaline solution, wherein the acidic solution is a 0.5 mol / L H2SO4 solution, and the alkaline solution is a 1 mol / L KOH solution.

[0026] Compared with the prior art, the present invention has the following technical effects:

[0027] (I) The high-efficiency electrocatalytic composite material of the present invention significantly broadens the application conditions of hydrogen evolution reaction and enhances the ability to achieve a better overpotential under both acidic and alkaline conditions. Under acidic conditions, the overpotential η 10 is 94mV. Under alkaline conditions, the overpotential η 10 The high-efficiency composite material PrCuCoP / NF has a high current density (700mAcm -2 ) can maintain better reaction activity.

[0028] (II) The PrCuCoP / NF high-efficiency electrocatalytic composite material of the present invention has an increased microrod diameter and a rougher surface due to the introduction of Pr and Cu elements for co-doping, which can provide more active sites and is beneficial to improving the electrocatalytic activity.

[0029] (III) In the present invention, the Pr element on the surface of the high-efficiency electrocatalytic composite material exists in the form of Pr2O3, and the Cu element exists in the form of CuO and / or CuO2. The formation of oxides provides more active sites for the hydrogen evolution reaction process under high current density.

[0030] (IV) The high-efficiency electrocatalytic composite material of the present invention has a more regular grid structure and stands on the NF substrate in an array-like manner in the vertical direction. In particular, the electrochemical specific surface area and conductivity of the composite material PrCuCoP / NF are both high, which can increase the active sites of the catalyst and the exposure of the active sites, thereby improving the catalytic performance.

[0031] (V) The electrochemical active area ECSA of the high-efficiency electrocatalytic composite material of the present invention is 532.75 cm 2 , compared with the monomer CoP / NF, the ECSA of the composite material is larger.

[0032] (VI) The electron mass transfer efficiency of the high-efficiency electrocatalytic composite material of the present invention is significantly enhanced. Compared with the monomer CoP / NF, the amorphous structure constructed by the high-efficiency composite material PrCuCoP / NF can effectively promote the separation and transfer of electrons.

[0033] (VII) The high-efficiency electrocatalytic composite material PrCuCoP / NF of the present invention has excellent stability under both acidic and alkaline conditions, and can reach an initial current density of -10 mA cm -2 At a voltage of , the current density remains essentially unchanged for at least 48 h. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the SEM image of the PrCuCoP / NF high-efficiency electrocatalytic composite material.

[0035] Figure 2 This is the TEM image of the PrCuCoP / NF high-efficiency electrocatalytic composite material.

[0036] Figure 3 This is the full XPS spectrum of the PrCuCoP / NF high-efficiency electrocatalytic composite material.

[0037] Figure 4 This is the XRD spectrum of the PrCuCoP / NF high-efficiency electrocatalytic composite material.

[0038] Figure 5 This is the linear voltammetric scan LSV diagram of the PrCuCoP / NF high-efficiency electrocatalytic composite material under 0.5 mol / L H2SO4 acidic conditions.

[0039] Figure 6 This is the linear voltammetric scan LSV diagram of the PrCuCoP / NF high-efficiency electrocatalytic composite material under 1 mol / L KOH alkaline conditions.

[0040] Figure 7 It is the stability diagram of PrCuCoP / NF high-efficiency electrocatalytic composite material under acidic and alkaline conditions.

[0041] The specific contents of the present invention are further explained in detail below in conjunction with embodiments. DETAILED DESCRIPTION

[0042] It should be noted that, unless otherwise specified, all raw materials and instruments used in the present invention are those known in the prior art. For example, sodium hypophosphite is commercially available sodium hypophosphite.

[0043] The instruments and materials used in the present invention are:

[0044] ESG60-4 electronic balance (Shenyang Longteng Electronic Weighing Instrument Co., Ltd.), CHI660B Chenhua electrochemical workstation (Shenyang Longteng Electronic Weighing Instrument Co., Ltd.), DZ-2BC vacuum drying oven (Tianjin Test Instrument Co., Ltd.), 217-01 double salt bridge calomel electrode (Shanghai Yidian Scientific Instrument Co., Ltd.), 217-01 double salt bridge calomel electrode (Shanghai Yidian Scientific Instrument Co., Ltd.), 213 metal platinum sheet electrode (Shanghai Precision Scientific Instrument Co., Ltd.), SK3-3-12-5 energy-saving vacuum tube furnace (Hangzhou Zhuochi Instrument Co., Ltd.).

[0045] Sodium hypophosphite (analytical grade, Xi'an Haimeng Experimental Technology Co., Ltd.), cobalt nitrate hexahydrate (analytical grade, Xi'an Haimeng Experimental Technology Co., Ltd.), urea (analytical grade, Xi'an Haimeng Experimental Technology Co., Ltd.), ammonium fluoride (analytical grade, Xi'an Haimeng Experimental Technology Co., Ltd.), copper nitrate trihydrate (analytical grade, Shanghai McLean Biochemical Technology Co., Ltd.), sodium chloride (analytical grade, Xi'an Haimeng Experimental Technology Co., Ltd.), ferric nitrate nonahydrate (analytical grade, China Pharmaceutical (Group) Shanghai Chemical Reagent Company), praseodymium chloride hexahydrate (analytical grade, Xi'an Dao Biochemical Science and Trade Co., Ltd.), nickel foam (99.8%, Changde Liyuan nickel foam).

[0046] The overall inventive concept of the present invention is: the Cu element has a strong electrical conductivity and can produce a strong electronic interaction with transition metal compounds to change the electron density. The unique 4f0 electron orbital structure of rare earth metal cations gives it excellent magnetic, optical, electrical and other properties. Rare earth elements usually exist in an oxidation state of +3, and the 4f electronic structure of the Pr element has a strong electronic regulation ability. Cobalt-based compounds have the potential to achieve multifunctional catalysis. After the Cu element and the Pr element are co-doped with CoP, the atomic distribution on its surface is regulated. The Pr element exists in the form of Pr2O3, and the Cu element exists in the form of CuO and CuO2. The formation of oxides provides more active sites for the hydrogen evolution reaction process under high current density.

[0047] It should be noted that the raw materials in the present invention and their corresponding molecular formulas or abbreviations are: sodium hypophosphite (NaH2PO2), cobalt nitrate hexahydrate (Co(NO3)3·6H2O), urea (CH4N2O), ammonium fluoride (NH4F,), copper nitrate trihydrate (Cu(NO3)3·3H2O), praseodymium chloride hexahydrate (PrCl3·6H2O) and nickel foam (NF, 99.8%).

[0048] The room temperature in the present invention refers to the natural environment temperature during the production process. Usually, the temperature is generally within the range of 20±10°C.

[0049] The water in the present invention is deionized water.

[0050] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.

[0051] Embodiment 1:

[0052] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0053] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0054] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 1:1.

[0055] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0056] PrCuCoP / NFPr:Cu=1:1.

[0057] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment comprises the following steps:

[0058] Step 1: Mix 582 mg Co(NO3)3·6H2O, 721 mg CH4N2O and 74 mg NH4F, add to a 2×4 cm 2 NF water to obtain a mixed solution.

[0059] Step 2: Add 400 mg of NaH2PO2 to the mixed solution in step 1 for phosphating at a temperature of 300° C. for 2 h and a heating rate of 2° C. / min to obtain a monomer CoP / NF substrate.

[0060] Step three, mix 355 mg of PrCl3·6H2O and 483 mg of Cu(NO3)3·3H2O, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 1:1, add to 80 mL of deionized water, and stir at room temperature for 5 minutes using magnetic stirring to form an electrolyte.

[0061] Step 4: Under stirring conditions, the monomer CoP / NF substrate obtained in step 2 is placed in the electrolyte obtained in step 3, and an electrodeposition reaction is carried out at room temperature. The current density of the electrodeposition is 0.25 mA, and the deposition time is 300 s.

[0062] Step 5: After the reaction in step 4 is completed, the mixture is repeatedly rinsed with water and vacuum dried at 60° C. for 6 h to obtain a PrCuCoP / NF high-efficiency electrocatalytic composite material, namely, PrCuCoP / NFPr:Cu=1:1.

[0063] Embodiment 2:

[0064] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0065] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0066] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 1:2.

[0067] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0068] PrCuCoP / NFPr:Cu=1:2.

[0069] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 237 mg and 644 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 1:2.

[0070] Embodiment 3:

[0071] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0072] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0073] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 1:3.

[0074] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0075] PrCuCoP / NFPr:Cu=1:3.

[0076] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 178 mg and 725 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 1:3.

[0077] The SEM image of the PrCuCoP / NF high-efficiency electrocatalytic composite material prepared in Example 3 is as follows: Figure 1 As shown in the TEM image Figure 2 As shown in the figure, when the Pr:Cu molar ratio is 1:3, the electronic structure of PrCuCoP / NF can be effectively adjusted, and its active sites and conductivity can be increased. In the HRTEM results of PrCuCoP / NF, there is a layered structure between PrCuCoP and CoP substrate, and there are a large number of amorphous structures, which is conducive to accelerating the electron mass transfer efficiency in the hydrogen evolution reaction, promoting the generation of adsorbed hydrogen (M Hads), and effectively reducing the reaction energy barrier of Heyrovsky, the rate-determining step in the hydrogen evolution reaction, thereby improving the activity of the hydrogen evolution reaction.

[0078] The full XPS spectrum of this example is as follows Figure 3 As shown in the figure, the appearance of characteristic peaks of Pr, Cu, Co, and P indicates the successful preparation of the material. In addition, the possible source of C is the vacuum chamber of the test instrument, while the source of O is due to the inevitable oxidation of the material in contact with air.

[0079] The XRD spectrum of this example is as follows Figure 4As shown, the monomer CoP / NF substrate and the PrCuCoP / NF high-efficiency electrocatalytic composite material prepared from Example 3 are both rich in the crystalline phases of (Co2P#32-0306) and (CoP#29-0497). In addition, the presence of the crystalline phases of (Cu2O#32-0306) and (Pr2O3#32-0306) also proves the successful preparation of the PrCuCoP / NF material.

[0080] Embodiment 4:

[0081] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0082] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0083] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 1:4.

[0084] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0085] PrCuCoP / NFPr:Cu=1:4.

[0086] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 142 mg and 773 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 1:4.

[0087] Embodiment 5:

[0088] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0089] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0090] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 2:1.

[0091] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0092] PrCuCoP / NFPr:Cu=2:1.

[0093] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 474 mg and 322 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 2:1.

[0094] Embodiment 6:

[0095] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0096] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0097] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 3:1.

[0098] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0099] PrCuCoP / NFPr:Cu=3:1.

[0100] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 533 mg and 242 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 3:1.

[0101] Embodiment 7:

[0102] This embodiment provides a PrCuCoP / NF high-efficiency electrocatalytic composite material, including a monomer CoP / NF substrate, on which Pr elements and Cu elements are co-doped.

[0103] The raw material of Pr element is PrCl3·6H2O; the raw material of Cu element is Cu(NO3)3·3H2O.

[0104] The molar ratio between the Pr element in PrCl3·6H2O and the Cu element in Cu(NO3)3·3H2O is 4:1.

[0105] The PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is recorded as:

[0106] PrCuCoP / NFPr:Cu=4:1.

[0107] The preparation method of the PrCuCoP / NF high-efficiency electrocatalytic composite material in this embodiment is basically the same as that in Example 1, with the only difference being that in step three, the masses of PrCl3·6H2O and Cu(NO3)3·3H2O are 568 mg and 194 mg, respectively, that is, the molar ratio of the Pr element in PrCl3·6H2O to the Cu element in Cu(NO3)3·3H2O is 4:1.

[0108] Embodiment 8:

[0109] This example shows the application of the PrCuCoP / NF high-efficiency electrocatalytic composite material as a catalyst for electrocatalytic hydrogen evolution at high current density.

[0110] The PrCuCoP / NF high efficiency electrocatalytic composite material of this embodiment adopts the PrCuCoP / NF high efficiency electrocatalytic composite material given in Examples 1 to 7.

[0111] The conditions for electrocatalytic hydrogen evolution in this embodiment are: the reaction area of ​​the PrCuCoP / NF high-efficiency electrocatalytic composite material is 0.5×1 cm 2 , current density is 700mAcm -2 The solution for the hydrogen evolution reaction is an acidic solution or an alkaline solution, wherein the acidic solution is a 0.5 mol / L H2SO4 solution, and the alkaline solution is a 1 mol / L KOH solution.

[0112] Figure 5 This is the LSV diagram of PrCuCoP / NF in 0.5mol / LH2SO4 acidic environment with different molar ratios of Pr and Cu. Figure 5 It can be seen that the PrCuCoP / NF prepared in Example 3 has the best HER performance under acidic conditions.

[0113] Figure 6 This is the LSV diagram of PrCuCoP / NF in 1mol / LKOH alkaline environment with different molar ratios of Pr and Cu. Figure 6 It can be seen that the PrCuCoP / NF prepared in Example 3 also has excellent HER performance under alkaline conditions.

[0114] The stability of the PrCuCoP / NF high-efficiency electrocatalytic composite material in acidic and alkaline environments given in Example 3 is as follows: Figure 7As shown. Figure 7 It can be seen that the PrCuCoP / NF given in Example 3 ensures that the initial current density reaches -10mAcm -2 At a voltage of , the current density can be kept basically unchanged for at least 48 hours in both acidic and alkaline environments, indicating that it has good stability.

Claims

1. A PrCuCoP / NF high-efficiency electrocatalytic composite material, comprising a monomer CoP / NF substrate, characterized in that: The monomer CoP / NF substrate is co-doped with Pr and Cu elements; The molar ratio between the Pr element in the raw material of the Pr element and the Cu element in the raw material of the Cu element is (1 to 4):(1 to 4).

2. The PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 1, characterized in that: The Pr element exists in the form of Pr2O3; the Cu element exists in the form of CuO and / or CuO2.

3. The PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 1, characterized in that: The raw material of the Pr element is PrCl3·6H2O; the raw material of the Cu element is Cu(NO3)3·3H2O.

4. The PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 1, characterized in that: The molar ratio between the Pr element in the raw material of the Pr element and the Cu element in the raw material of the Cu element is 1:(1-4) or (1-4):

1.

5. The PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 1, characterized in that: The Pr element and the Cu element are co-doped on the monomer CoP / NF substrate in the form of an electrodeposition reaction.

6. The PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 5, characterized in that: The process of the electrodeposition reaction is as follows: placing in a standard three-electrode system, the current density of the electrodeposition reaction is 0.25 mA, and the time of the electrodeposition reaction is 300 s.

7. A method for preparing the PrCuCoP / NF high-efficiency electrocatalytic composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Step 1, mixing Co(NO3)3·6H2O, CH4N2O and NH4F, and adding the mixture into water containing nickel foam to obtain a mixed solution; Step 2, adding NaH2PO2 to the mixed solution in step 1 for phosphating to obtain a monomer CoP / NF substrate; Step 3, dissolving the raw material of the Pr element and the raw material of the Cu element in water, and stirring to form an electrolyte; Step 4: placing the monomer CoP / NF substrate obtained in step 2 into the electrolyte obtained in step 3 under stirring conditions, and performing an electrodeposition reaction at room temperature; Step 5: After the reaction in step 4 is completed, the mixture is repeatedly rinsed with water and vacuum dried to obtain a PrCuCoP / NF high-efficiency electrocatalytic composite material.

8. The method for preparing the PrCuCoP / NF high-efficiency electrocatalytic composite material according to claim 7, characterized in that: In step 1, the specification of the NF is 2×4 cm 2 ; In step 2, the phosphating time is 2 hours, the phosphating temperature is 300°C, and the phosphating heating rate is 2°C / min; In step 5, the vacuum drying temperature is 60° C. and the vacuum drying time is 6 hours.

9. Use of the PrCuCoP / NF high-efficiency electrocatalytic composite material as claimed in any one of claims 1 to 6 as a catalyst for electrocatalytic hydrogen evolution at high current density.

10. The use according to claim 9, characterized in that The conditions for electrocatalytic hydrogen evolution are as follows: the reaction area of ​​the PrCuCoP / NF high-efficiency electrocatalytic composite material is 0.5×1 cm 2 , current density is 700mAcm -2 The solution for the hydrogen evolution reaction is an acidic solution or an alkaline solution, wherein the acidic solution is a 0.5 mol / L H2SO4 solution, and the alkaline solution is a 1 mol / L KOH solution.